PENGEMBANGAN UMKM DI MASA PANDEMI MELALUI OPTIMALISASI TEKNOLOGI - Hartana Hartana; Ni Luh Wayan Yasmiati (Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
Strengthening MSMEs in the midst of the Covid-19 pandemic through optimizing digital marketing is one of the most effective marketing strategies and must be done equally for all MSME actors. Digital marketing is a promotional activity and market search through digital media online by utilizing various means, such as social networks. Digital marketing on the one hand, makes it easier for business people to monitor and provide all the needs and desires of potential consumers, on the other hand, potential consumers can also search for and obtain the desired product information only by exploring the virtual world so as to facilitate the search process without leaving the house. Digital marketing is able to reach all people wherever they are without being hindered by geographical or time restrictions, even during this Covid-19 pandemic. Community needs can be met without worrying about having to interact with other people directly. The use of digital marketing provides new hope for MSMEs to survive in the midst of a pandemic and develop into a center of economic power because the digital era is unavoidable. The development of digital technology allows MSME actors to market their products online and make transactions through the online banking system as well. This certainly makes transactions easier in the midst of pandemic policies that limit direct interaction between traders and buyers. This can be a stimulant for the development of entrepreneurship and the sustainability of MSMEs. Therefore, it is not surprising that one of the strategies of MSME actors to block the domino effect of the current pandemic is more focused on the use of social media than the development of a site. This condition is one of the reasons to help empower MSME actors by providing assistance in the form of assistance in the utilization and optimization of the use of digital media to conduct massive promotions in order to have a significant impact on awareness of target consumers in the hope of increasing sales of MSME products in the midst of the Covid-19 pandemic. 19.